(untitled) (The Conference Hub, 2026)
The rapid evolution of generative artificial intelligence (AI) has become one of the most transformative technological developments of the 21st century. Generative AI systems, including large language models, image and video generators, and automated code-writing tools, are now widely used across industries such as education, healthcare, finance, government, and cybersecurity itself. These systems are capable of creating human-like text, realistic images, synthetic voices, and even complex software code. While generative AI offers significant opportunities for innovation, efficiency, and economic growth, it also introduces serious cybersecurity challenges that must be carefully addressed.